Analysis Factor Reason Incident Missile File Record Medical In Room Hospital Filing Dr. Soeratno Gemolong - Al-Hadri, Cecilia Farrona; Suryaningrum, Tarisa Eka (Medicor : Journal of Health Informatics and Health Policy, 2024)
In health services in hospitals, medical record file missfiles often occur, thus making health services note optimal. The patient's personal data and medical data are in the medical records files, if the medical records file is not immediately found due to a missfile incident, the officer cannot take medical action immediately. The The purpose of this research is to analyze the factors that cause missfiles in the filing room of RSUD dr. Soeratno Gemolong. In this research, the type of research used by researchers is a qualitative research with a descriptive approaches. The study population was all medical records units officers, totaling 19 officers consisting of the head of medical records, Assembling, Indexing Coding, Analyzing Reporting, and Filing at RSUD dr. Soeratno Gemolong. The sample in this study were medical record unit officers in the Filing section, totaling 5 officers at Dr. Soeratno Gemolong Hospital. The sampling technique is purposive sampling technique. Data collection instruments through interviews. Data analysis in this study was carried out using descriptive analysis. Based on the results of research at dr. Soeratno Gemolong found that there were 19.13% missfiles, namely 88 documents, while 80.86% did not missfile, namely 372 documents out of 460 documents entered in one month. Factors causing Missfile: knowledge, work experience, negligence of officers, work discipline.